A low‐profile dual‐band dual‐polarized tightly spaced antenna array with artificial magnetic conductor surface for 5G micro base station application. Issue 7 (19th April 2022) - Duan, Zhu; Rui, Jie; Xu, Li‐Jie; Wen, Geyi
Abstract: A novel low‐profile dual‐band dual‐polarized tightly spaced antenna array with artificial magnetic conductor (AMC) surface for 5G micro base station application is proposed in this paper. The main radiating element is a pair of crossed annular dipoles, excited with two different resonant modes in orthogonal arms. The radiator is backed by an additional dual‐band AMC reflector located 0.03 λ0 below. Four such elements are then tightly spaced to form an antenna array. By replacing the four interior AMC patches with an S‐shaped patch, the strong coupling at the lower band is successfully mitigated. The final results show that the dual‐band array has an impedance bandwidth of 13.8% (2.44–2.80 GHz) and 6% (4.75–5.03 GHz), covering the sub‐6GHz band of China Mobile. The antenna's peak realized gain is 10 dBi at the lower band and 13.7 dBi at the upper band, making it a good candidate for 5G micro base stations.